Pengaruh Penyuluhan Terhadap Pengetahuan Ibu tentang PMBA Usia 6-24 Bulan di Banjar Beluhu, Desa Suter, Kecamatan Kintamani, Kabupaten Bangli - -, Seniawati; Dewantari, Ni Made; Widarti, I Gusti Agung Ari (Poltekkes Kemenkes Denpasar dan DPD PERSAGI Bali, 2025)
Infant and Child Feeding is one of the government's programs aimed at reducing child mortality rates and improving the quality of life for mothers. According to survey data from the Kintamani IV Public Health Center, there is still a prevalence of undernourished toddlers in Banjar Beluhu, Desa Suter, at 32.78%, which is attributed to the lack of maternal knowledge about Infant and Child Feeding. The objective of this study is to determine the effect of health education on maternal knowledge regarding Infant and Child Feeding for children aged 6-24 months in Banjar Beluhu, Desa Suter, Kecamatan Kintamani, Kabupaten Bangli. This type of research is experimental with a quasi-experimental one-group pretest-posttest design. A pre-test was administered before the health education session, followed by a post-test. The analysis used was the Paired t-test. Knowledge before the health education showed 17% in the moderate category, while 83% were in the low category. After the health education, 55% were in the good category, and 45% were in the moderate category. The Paired t-test indicated a significant effect on maternal knowledge before and after the health education on infant and child feeding (p 0.05).